(untitled) (Universitas Scientiarum, 2014)
In high mountain ecosystems, Hepaticae is prominent and are essential to regulate and maintain hydrological cycles; they also contribute to nutrient recycling. We sampled five different substrates (decomposing matter, tree base, bare soil, rocks and flush root) of the "Robledales de Tipacoque" Natural Park and recorded 52 species of Hepaticae belonging to 21 genera and 12 families. The families having the highest number of species were the Plagiochilaceae with 22 (40.7%) and Lejeuneaceae with nine (16.6%), and the substrates with the highest number of species were decaying matter (30), followed by rock (22). The floristic composition in altitudinal belts is so distinct, that species of Hepaticae were found constrained to one altitudinal range.